Stream Sediment Geochemical Survey around Mildo and Its Environs, Madagali, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Saleh, M.B.; Hassan, A. (IJRDO-Journal of Applied Science, 2017)
In an attempt to explore the mineral potentials of Mildo area, geology and stream sediments geochemical survey around Mildo and its environs, Madagali area, Northeastern Nigeria was carried out. The area is part of Mandara Mountains. The Mandara Mountains together with the adjacent Hawal and Adamawa Massif form the northeastern basement complex. Stream sediments were collected at the confluence points of two or more streams mostly at a depth of 20 – 30cm. The stream sediment samples were analyzed for trace and major elemental concentration using XRF analytical method. The result of the geochemical analysis was thereafter subjected to statistical analysis. Elements of high concentrations were identified and they include Ba, Ti, Fe, Zn, Cu, Hg, Cd, Co, Zr, Sr and Ag. Locations SSP4 and SSP13 have concentrations of these elements in high values. We speculate that high concentration of Ag can be associated with mineralization of gold and other Platinum Group Metals in the area. Although, most elements studied have high concentrations, but they fall short of threshold values to be considered as anomalous to constitute an economic deposit. However, we recommend further surveys in the vicinity of areas with highest concentrations for possible location of economic deposits upstream